Leaf anatomy of six species of Heliotropiaceae Schrad. from the Brazilian semi-arid region - Elisabeth Tölke; Sandra Maria Carmello-Guerreiro; José Iranildo Miranda de Melo (Biotemas)
The family Heliotropiaceae has more than 450 species, mainly distributed in the tropics and subtropics. In Brazil, it is represented by the genera Euploca Nutt., Heliotropium L., Myriopus Small and Tournefortia L. The aim of this study was to describe the leaf anatomy of six species of Heliotropiaceae recorded in the semi-arid region of Brazil: E. polyphylla (Lehm.) J.I.M. Melo & Semir, E. procumbens (Mill.) Diane & Hilger, H. angiospermum Murray, H. curassavicum L., M. rubicundus (Salzm. ex DC.) Luebert and M. salzmannii (DC.) Diane & Hilger. Besides contributing to the knowledge of the anatomy of the representatives of the family in the Caatinga (Brazilian savannah), we also sought to determine and highlight the anatomical features adaptive to the region and to identify features with potential diagnostic value. Leaf structures were analyzed by light microscopy and scanning electron microscopy. Additional tests were also carried out to detect starch and total lipids. The morphological variation and the distribution of trichomes were the most relevant features for species diagnosis. The distribution of stomata in M. salzmannii and H. angiospermum differed from that described in other papers, which demonstrates the anatomical plasticity of these species. This is the first report describing the leaf blade of M. rubicundus.